Tildrakizumab in the treatment of plaque psoriasis in an HIV+ patient: a case report and literature review of anti-interleukin drugs - Viviana Lora; Dario Graceffa; Monia Di Prete; Carlo Cota (PAGEPress Publications, 2024)
Treatment of psoriasis associated with human immunodeficiency virus (HIV) infection is challenging due to the high incidence of comorbidities and polypharmacy and the lack of evidence on the efficacy and safety of available drugs in these patients. Therefore, clinical or anecdotal reports provide useful indications for therapy decision-making. A 64-year male with plaque psoriasis (Psoriasis Area and Severity Index=14.3) infected with HIV for 4 years, with hypercholesterolemia, hypertension, and impaired quality of life (Dermatology Life Quality Index=14) was resistant to topical therapy and acitretin. Tildrakizumab 200 mg was started, obtaining Psoriasis Area and Severity Index=0 at week 16 which was maintained after 13 months of follow-up. No adverse event was reported, and immune cell levels were unchanged. This is the first report on the treatment of psoriasis with tildrakizumab in an HIV+ patient. A literature search showed that prior to this patient, 38 HIV+ subjects had been treated with anti-cytokine agents for psoriasis.